A Multicenter Retrospective Study Examining Complication Rates Following Syndesmotic Screw Removal. Issue 4 (22nd October 2020) - Shoap, Seth C.; Freibott, Christina; Baumbach, Sebastian F.; Herterich, Viktoria; Polzer, Hans; Vosseller, J. Turner
Category: Ankle; Trauma Introduction/Purpose: 20% of ankle fractures in the US involve a concomitant injury to the syndesmosis. What syndesmotic fixation is most appropriate is a subject of some debate. When syndesmotic screws are used, many of the variables surrounding treatment are unclear. One recent study quoted an alarmingly high rate of complications after syndesmotic screw removal (reference). The authors of the current study have routinely removed syndesmotic screws with little in the way of complications. This multicenter study was conducted in order to compare complication rates following syndesmotic screw removal in two institutions that regularly remove syndesmotic screws. Methods: Patient selection was based on the ankle fracture databases of the orthopedic department in two major academic institutions. At both institutions, databases includes all patients treated surgically for any type of ankle fracture between 01/2010 and 12/2016 in patients older than 18 years. Patients meeting the following inclusion criteria were selected: patients suffering any type of an acute, closed ankle fracture, syndesmotic disruption treated using a syndesmotic screw, removal of the syndesmotic screw in the same institution, and patient chart available for review. Exclusion criteria: pilon fractures, and tibial shaft fractures, as well as any postoperative infection following the original osteosynthesis. Data from the chart included age, sex, height, weight, BMI, days until screw removal, smoking status, alcohol use, diabetes status, and any wound complications or complication related to the screw removal. A logistic regression analysis was conducted to assess for predictors of wound complications after syndesmotic screw removal. Results: In our cohort of 152 patients, 1.3% of patients had wound complications. When looking at the cohorts separately, there was a reported wound complication in 3.2% (1 out of 31) of patients in institution 1, whereas there was a 0.83% (1 out of 121) wound complication rate in the cohort at institution 2 (p=0.296). There were no significant predictors of wound complications when looking at age (p=0.992), height (p=0.511), weight (p=0.735), BMI (p=0.755), days until screw removal (p=0.80), sex (p=0.404), smoking status (p=0.999), alcohol use (p=0.102), or diabetes status (p=0.269). Chi-square analysis revealed that there was not a significant association between wound complication and smoking (p=0.177), alcohol use (p=0.461) and diabetes status (p=0.602) in each cohort. Conclusion: A recent study reported a high rate of complications as a result of syndesmotic screw removal. Our multicenter study found minimal complications after syndesmotic screw removal. Further, out of two patients that did have reported complications, neither required secondary intervention as a form of treatment. These complications were considered minor and were treated with oral antibiotics.